2017
DOI: 10.1186/s12859-016-1428-4
|View full text |Cite
|
Sign up to set email alerts
|

An internet-based bioinformatics toolkit for plant biosecurity diagnosis and surveillance of viruses and viroids

Abstract: BackgroundDetection and preventing entry of exotic viruses and viroids at the border is critical for protecting plant industries trade worldwide. Existing post entry quarantine screening protocols rely on time-consuming biological indicators and/or molecular assays that require knowledge of infecting viral pathogens. Plants have developed the ability to recognise and respond to viral infections through Dicer-like enzymes that cleave viral sequences into specific small RNA products. Many studies reported the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
(57 reference statements)
1
34
0
1
Order By: Relevance
“…Small RNA deep sequencing analysis of Citrus sp. has revealed that the Petuvirus -like EVEs representing Citrus endogenous pararetrovirus spawn predominantly 24-nt siRNAs along with less abundant 21-nt and 22-nt siRNAs ( Barrero et al, 2017 ), further supporting the involvement of RdDM. Likewise, the Petuvirus -like EVE sequences at the centromeres of Fritillaria imperialis are associated with predominantly 24-nt siRNAs and methylated cytosines at both symmetric (CG, CHG) and asymmetric (CHH) sites, which is a clear signature of RdDM ( Becher et al, 2014 ).…”
Section: Biogenesis and Function Of Viral Sirnasmentioning
confidence: 91%
See 2 more Smart Citations
“…Small RNA deep sequencing analysis of Citrus sp. has revealed that the Petuvirus -like EVEs representing Citrus endogenous pararetrovirus spawn predominantly 24-nt siRNAs along with less abundant 21-nt and 22-nt siRNAs ( Barrero et al, 2017 ), further supporting the involvement of RdDM. Likewise, the Petuvirus -like EVE sequences at the centromeres of Fritillaria imperialis are associated with predominantly 24-nt siRNAs and methylated cytosines at both symmetric (CG, CHG) and asymmetric (CHH) sites, which is a clear signature of RdDM ( Becher et al, 2014 ).…”
Section: Biogenesis and Function Of Viral Sirnasmentioning
confidence: 91%
“… Xu et al (2017) have reconstructed the virome of tomatoes in China by sequencing small RNAs from 170 samples and identified 22 viruses representing 12 genera of RNA and DNA viruses and 2 viroids (see “ Xu et al, 2017 ” in Supplementary Tables S1 , S2 ): the complete genomes were reconstructed from small RNAs by de novo and reference-based assembly for 13 of the 22 viruses and near complete ones (>90% genome sequence) for another 5 viruses. Likewise, small RNA-omics has been successfully used for reconstruction of the complex viromes of vegetatively cultivated sweet potatoes ( Kreuze et al, 2009 ; Cuellar et al, 2011 ; Kashif et al, 2012 ; De Souza et al, 2013 ; Mbanzibwa et al, 2014 ; Cuellar et al, 2015 ; Untiveros et al, 2016 ; Cao et al, 2017 ; see Supplementary Tables S1 and Supplementary List S1 ) and grapevines ( Pantaleo et al, 2010 ; Zhang et al, 2011 , 2014 ; Alabi et al, 2012 ; Giampetruzzi et al, 2012 ; Wu et al, 2012 ; Glasa et al, 2014 , 2015 ; Seguin et al, 2014 ; Maliogka et al, 2015 ; Chiumenti et al, 2016a ; Eichmeier et al, 2016 ; Barrero et al, 2017 ; Czotter et al, 2018 ; see Supplementary Tables S1 , S2 and Supplementary List S1 ), which led to identification of novel RNA and DNA viruses and viroids among other virome components. Mwaipopo et al (2018) have identified 15 viral species from 10 genera of RNA and DNA viruses in the virome of common bean (see Supplementary Table S1 and Supplementary List S1 ).…”
Section: Toward More Exhaustive Reconstruction Of Complex Viromes By mentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, accurate monitoring of newly emergent strains, that can occur by introduction or recombination, can be used for timely containment actions. A second application is an eco-genomic survey in certain crops or for certain virus groups, that is, run necessarily as a pilot study in geographic areas (see the example of Australia) [ 91 ] to check the virus status already present, and avoid the introduction of unwanted agents. Pursuing the former objective, Zablocki & Pietersen [ 92 ] and Read & Pietersen [ 93 ] provided evidence through HTS analysis regarding the isolates associated with the breaking of CTV cross-protection in grapefruit industry, characterizing recombination events, and fine population mapping, even at a single gene level.…”
Section: Application Of High-throughput Sequencing Technology To Dmentioning
confidence: 99%
“…Since contigs assembled from sRNA reads using the above-cited pipeline were relatively short, we performed an additional assembly of sRNA reads using SPAdes ( Bankevich et al, 2012 ; Nurk et al, 2013 ). The parameter “careful” and combined k-mer sets of 15, 17, 19, and 21 were applied to produce long assembled sequences ( Barrero et al, 2017 ). For each of the two sequencing approaches, all of the contigs matching potyvirus sequences were further assembled to obtain a complete or near complete viral genome sequence using CLC Genomic Workbench 10 (Qiagen).…”
Section: Methodsmentioning
confidence: 99%